The procedure of reviewing publications and ethics statement - Editorial Team (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2025)
The procedure of reviewing publications The procedure of reviewing articles published in the journal “Ordines Militares Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders” is as follows: Two independent reviewers are appointed to define the academic value of each text sent to the editorial office. Each reviewer of a given text is an employee of scientific institutions in the country other than the country of origin of the author of the article. Neither of the reviewers knows the identity of the other reviewer. The names of the reviewers of given texts remain secret and they are kept by the editorial team. However, in each volume there appears a list of reviewers cooperating with the editorial staff. Reviews are in a written form. To publish an article it is necessary to obtain the agreement of both reviewers who express and justify their opinions concerning the academic nature and the scientific value of a reviewed text. Ethics statement The journal “Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders” implements ethics rules as well as “ghostwriting”, “guest authorship” and plagiarism detection procedures, which are prepared in accordance with COPE standards. For the details visit http://www.apcz.pl/ czasopisma/index.php/OM/about/index or http://www.ordinesmilitares.umk.pl